2008
DOI: 10.1007/s10909-008-9819-1
|View full text |Cite
|
Sign up to set email alerts
|

High Frequency Sound in Superfluid 3He-B

Abstract: We present measurements of the absolute phase velocity of transverse and longitudinal sound in superfluid 3 He-B at low temperature, extending from the imaginary squashing mode to near pair-breaking. Changes in the transverse phase velocity near pair-breaking have been explained in terms of an order parameter collective mode that arises from f -wave pairing interactions, the so-called J = 4 − mode. Using these measurements, we establish lower bounds on the energy gap in the B-phase. Measurement of attenuation … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…The transverse sound with the Faraday effect has been established as a high-resolution spectroscopy for lowlying bosonic and fermionic excitations in 3 He-B. 56,[375][376][377] Among the series of experiments, Davis et al 56 observed the unexpected behavior of the attenuation in the frequency range of 1.6 ω/∆ 0 2.0. The attenuation becomes satu-rated to the temperature-independent value at low T , which is anomalously larger than that expected from theoretical calculation.…”
Section: Observations Of Surface Bound States In 3 He-bmentioning
confidence: 99%
“…The transverse sound with the Faraday effect has been established as a high-resolution spectroscopy for lowlying bosonic and fermionic excitations in 3 He-B. 56,[375][376][377] Among the series of experiments, Davis et al 56 observed the unexpected behavior of the attenuation in the frequency range of 1.6 ω/∆ 0 2.0. The attenuation becomes satu-rated to the temperature-independent value at low T , which is anomalously larger than that expected from theoretical calculation.…”
Section: Observations Of Surface Bound States In 3 He-bmentioning
confidence: 99%
“…The acoustic Faraday effect was first observed in [350]. The Faraday effect in transverse sound has been established as a high-resolution spectroscopy for low-lying bosonic excitation spectra in the bulk superfluid 3 He-B [351][352][353][354][355], because the quasiparticle states are empty up to the threshold of the pair breaking. In particular, the phase velocity of transverse sound waves observed in experiments is in quantitatively good agreement with that calculated from equation (328), while the unexpected behavior of the attenuation was observed in the frequency range 1.6 ω/ 0 2.0 in [353].…”
Section: Transverse Acousticsmentioning
confidence: 99%
“…For superfluid 3 He at zero pressure the energy gap is close to the BCS value, E = 1.764k B T c [20]. Besides the particle-like quasiparticles there are also hole-like quasiparticles where v g ↑↓ p. As depicted in Fig.…”
mentioning
confidence: 55%